1987
DOI: 10.1252/jcej.20.23
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical extraction of used automotive tire with water.

Abstract: Samplesfrom a used automotive tire were subjected to subcritical and supercritical extraction with water. Supercritical water wasfound to be almost as effective as supercritical /t-pentane. For a 9-mmcube sample the rate of supercritical extraction with water followed a first-order kinetics with an activation energy of 170kJ/mol. DynamicTGAdata for 0.13-0.35 mmsamples showedthat pyrolysis at temperatures of 690-730 K had almost the same activation energy as did supercritical extraction with water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…32,111,112 Thus far, gasification of 100% pure natural rubber has not been investigated. However, various studies reported that the gasification of tire rubber (consists of 40%-52.2% natural rubber 64,89,114 ) in an oxidizing medium under low-temperature conditions produced gaseous products, oil, and solid residues. 115 Ahmed and Gupta 116 performed pyrolysis and steam gasification of rubber tires at 800°C and 900°C to produce syngas.…”
Section: Gasificationmentioning
confidence: 99%
See 3 more Smart Citations
“…32,111,112 Thus far, gasification of 100% pure natural rubber has not been investigated. However, various studies reported that the gasification of tire rubber (consists of 40%-52.2% natural rubber 64,89,114 ) in an oxidizing medium under low-temperature conditions produced gaseous products, oil, and solid residues. 115 Ahmed and Gupta 116 performed pyrolysis and steam gasification of rubber tires at 800°C and 900°C to produce syngas.…”
Section: Gasificationmentioning
confidence: 99%
“…12,62,64,149,150 Many parameters affect hydrous pyrolysis; these parameters include particle size, reaction time, water to material ratio, heating rate, and operating atmosphere. Raw material quality also significantly influences the final product, Overall, temperature was found to be the most effective parameter that significantly affects product quantity and quality.…”
Section: 133mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the kinetics of scrap tyre pyrolysis have been carried out in the literature by means of techniques based on thermal analysis, such as thermogravimetry (TG), differential thermogravimetry (DTG) or differential scanning calorimetry (DSC) [24][25][26][27][28][29][30][31][32][33][34][35]. It must be pointed out that there are notable differences between the results obtained.…”
Section: Introductionmentioning
confidence: 99%